2021
DOI: 10.2147/copd.s289799
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Patterns in Patients with Chronic Obstructive Pulmonary Disease and Osteoporosis

Abstract: Objective Patients with chronic obstructive pulmonary disease (COPD) have a higher risk of osteoporosis. Few studies have addressed the prescription patterns in osteoporosis patients with COPD. The purpose of this study was to conduct a retrospective study of the prescription patterns in patients with COPD and osteoporosis in Taiwan. Methods The study was conducted with data from the Taiwan National Health Insurance Research Database from January 1, 2003, to December 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…found that osteoporosis was underdiagnosed among COPD patients. [ 9 ] The FEV1% predicted and FEV1/FVC ratios were significantly lower among osteoporotic patients than the nonosteoporotic ones, similar to a recent Taiwanese study. [ 13 ]…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…found that osteoporosis was underdiagnosed among COPD patients. [ 9 ] The FEV1% predicted and FEV1/FVC ratios were significantly lower among osteoporotic patients than the nonosteoporotic ones, similar to a recent Taiwanese study. [ 13 ]…”
Section: Discussionsupporting
confidence: 86%
“…Ethical approval for the study was obtained from the Medical Research and Ethics Committee, Ministry of Health Malaysia, with the following number: KKM/NIHEC/P19-528(11). [ 9 ]…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that several modifiable risk factors have been identified to have a role in osteoporosis prevention in COPD patients [ 17 ], several barriers still affect the lifestyle approach to osteoporosis in this patient, while a personalized osteoporosis approach is still far from being fully characterized [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“… 51 Conversely, experimental studies in animals have shown positive effects of metformin on bone loss, 23 , 24 and treatment with oral anti-diabetic medication seems to be associated with increased density bone mineral density, in contrast to insulin, for which lower intestinal absorption and increased urinary excretion of calcium, 16 as well as vitamin D regulation, might play a detrimental role. In cell cultures, osteogenic effects of metformin have been shown, 7 , 8 involving AMPK, mTOR (mechanistic target of rapamycin) complexes 1 and 2 and SIRT6 (sirtuin 6), with effects on NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells), a key pro-inflammatory transcription factor. It also increased OPG (osteoprotegerin) and decreased RANKL (receptor activator of NF-κB ligand) that is associated with osteoclastic activity and bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a major comorbidity of chronic obstructive pulmonary disease (COPD). [1][2][3][4][5][6][7] In addition to generic osteoporosis risk factors, such as female sex, higher age, smoking, cachexia and reduced physical capacity, a range of COPD-related risk factors are known to also increase osteoporosis risk, including the severity of pulmonary impairment, vitamin D deficiency, or systemic inflammation, 8,9 with systemic inflammation also an independent predictor of low bone mineral density (BMD) in patients with stable COPD. 10 Diabetes mellitus is also a common comorbidity in COPD, 11 and there is evidence that inflammatory pathways are involved in the pathogenesis of this disease.…”
Section: Introductionmentioning
confidence: 99%